Providing A Secure Environment For E-Commerce Sites Using SSL Technology - Maha A . Sayal (College of Education for Pure Sciences, 2020)
The issue of security on the Internet is at the top of the interest for most users, especially those who want to buy online and therefore find a large majority of users, especially new ones refrain from buying online and are afraid to go into such an experiment to complete the image and know more safety in the use of credit cards for some websites.      In order to increase confidence in online business transactions, we have proposed a safe environment for commercial sites by installing a private server and then submitting on certificate authority for digital certificates and obtaining Secure Socket Layer SSL technology, certificate it, and adding it to the server as well as hosting sites to secure its data and renew the certificate at expiration. This allows the business website owner to host that website on the secure server so the customer information and data will be protected.